Foreign Primary Listings and Earnings Quality - Cong, Ling Mei (EuroJournals, 2013)
Establishing the firm's primary listing on a foreign rather than the domestic capital market is a phenomenon virtually unique to firms from the People's Republic of China (PRC). This study determines whether earnings quality varies between PRC-domiciled firms with a foreign primary listing and counterparts with a domestic primary listing. It further investigates possible explanatory factors (i.e., place-of-listing and share type) influencing variations in earnings quality. The analysis is based on 501 PRC-domiciled firms with primary listings in the PRC, Hong Kong or Singapore. Earnings quality is measured using a ten [10] item benchmark derived from an analyst/practitioner based framework. The results provide support for the bonding theory indicating the earnings quality of PRC foreign primary listed firms is statistically significantly higher than domestic primary listed firms. Moreover, earnings quality difference exists across PRC firms with different places-of-listing and share types. Findings suggest risk-averse international investors may find purchasing shares in PRC-domiciled foreign primary listed firms (i.e., H-Share, Red- Chip, and S-Share) to be a more prudent investment option. The PRC authorities may need to improve the regulatory rigour to protect the nation's investment reputational capital.